2010
DOI: 10.1021/jf101319q
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Dry Matter Content in Potato Tubers by Low-Field Nuclear Magnetic Resonance (LF-NMR)

Abstract: The objective of this study was to develop a calibration model between time-domain low-field nuclear magnetic resonance (LF-NMR) measurements and dry matter (DM) content in single potatoes. An extensive sampling procedure was used to collect 210 potatoes from eight cultivars with a wide range in DM content, ranging from 16 to 28%. The exponential NMR relaxation curves were resolved into four mono-exponential components using a number of solution diagnostics. Partial least-squares (PLS) regression between NMR p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…The distributed exponential approach utilizes a regularization method to the inverse Laplace transformation yielding a continuous distribution of T 2 relaxation times (Provencher 1982). Mathematically, the distributed exponential fitting is ill-defined because it is sensitive to the constraints employed (Hansen et al, 2010;Martens and Thybo, 2000). In addition, there is a shorter T 2 relaxation component observed in the range of 10-15 ms.…”
Section: Resultsmentioning
confidence: 99%
“…The distributed exponential approach utilizes a regularization method to the inverse Laplace transformation yielding a continuous distribution of T 2 relaxation times (Provencher 1982). Mathematically, the distributed exponential fitting is ill-defined because it is sensitive to the constraints employed (Hansen et al, 2010;Martens and Thybo, 2000). In addition, there is a shorter T 2 relaxation component observed in the range of 10-15 ms.…”
Section: Resultsmentioning
confidence: 99%
“…To characterize these morphological structures, we suggested using 1 H Low Field (LF) NMR energy relaxation time analysis to generate multi‐dimensional graphics of the individual peaks representing PUFA's internal morphological and chemical aggregates, and to correlate it with the mechanism of PUFA oxidation and antioxidant efficacy. This technology is non‐destructive and does not require the use of solvents or sample preparation . Furthermore, we recently reported that 1 H LF‐NMR may evaluate both the primary and the secondary oxidation products in the same graph as separate peaks .…”
Section: Introductionmentioning
confidence: 99%
“…Low-field NMR relaxometry remains a nondestructive alternative, which is commonly used to investigate water contents, mobility, and interactions in matrix systems, such as plant organs 14,15 and particularly in imbibing and germinating seeds. 8,16−24 Deconvolution of the multiexponential curves obtained from longitudinal (T 1 ) and transverse (T 2 ) relaxations allows identifying groups and proportions of water protons that share environments, interactions or molecular exchange rates.…”
Section: Seed Germination Represents An Important Means Of Plants'mentioning
confidence: 99%